Prolonged duration of nonequilibrated Dirac fermions in neutral topological insulators. Issue 1 (December 2017) - Sumida, K.; Ishida, Y.; Zhu, S.; Ye, M.; Pertsova, A.; Triola, C.; Kokh, K.; Tereshchenko, O.; Balatsky, A.; Shin, S.; Kimura, A.
Abstract Topological insulators (TIs) possess spin-polarized Dirac fermions on their surface but their unique properties are often masked by residual carriers in the bulk. Recently, (Sb1−x Bix )2 Te3 was introduced as a non-metallic TI whose carrier type can be tuned fromn top across the charge neutrality point. By using time- and angle-resolved photoemission spectroscopy, we investigate the ultrafast carrier dynamics in the series of (Sb1−x Bix )2 Te3 . The Dirac electronic recovery of ∼10 ps at most in the bulk-metallic regime elongated to >400 ps when the charge neutrality point was approached. The prolonged nonequilibration is attributed to the closeness of the Fermi level to the Dirac point and to the high insulation of the bulk. We also discuss the feasibility of observing excitonic instability of (Sb1−x Bix )2 Te3 .